Solving the Equation: (m+1)(m+2) = 0
This equation is a simple quadratic equation in the form of a product of two factors equaling zero. To solve it, we can use the Zero Product Property.
Zero Product Property
The Zero Product Property states that if the product of two or more factors is zero, then at least one of the factors must be zero. In other words:
If a * b = 0, then either a = 0 or b = 0 (or both).
Solving the Equation
Applying this property to our equation, we have:
(m + 1)(m + 2) = 0
This means either:

m + 1 = 0
 Solving for m, we get: m = 1

m + 2 = 0
 Solving for m, we get: m = 2
Conclusion
Therefore, the solutions to the equation (m + 1)(m + 2) = 0 are m = 1 and m = 2. These are the values of 'm' that make the equation true.